Kearifan Lokal Petani Gula Aren Kecamatan Cijaku (Antara Tradisi dan Tuntutan Ekonomi) - Wahyuddin; Sulasno Sulasno; Fitria Agustin (Neolectura, 2020)
Palm sugar is a famous commodity from Lebak, Banten Province. Palm Sugar commodity is used as souvenirs from other regions in Indonesia, and is exported through the world market. The presence of palm sugar production business provides economic contribution to the local community. Palm Sugar Production mostly develops in Sobang, Malingping, Panggarangan, Cigemblong, Bayah, Ciharas, Cibeber, Muncang, Cimenga, Ciapus and Cijaku Districts. The purpose of this study was to determine the application of local wisdom of palm sugar farmers in Cijaku District, Lebak Regency. This study uses an empirical Historical method which is empirically objective, a method that aims to explain the development of the implementation of the Local Wisdom of Palm Sugar Farmers in Cijaku District, Lebak Regency, Banten Province. Data collection techniques were carried out using interview and informant methods that were determined purposively. That Local Wisdom is a hereditary tradition that preserves it is considered a noble value of ancestors. Local wisdom should not be eroded let alone erased because of economic demands both personal and regional.